Formation of planetary systems by pebble accretion and migration: Hot super-Earth systems from breaking compact resonant chains - Izidoro, Andre [UNESP]; Bitsch, Bertram; Raymond, Sean N.; Johansen, Anders; Morbidelli, Alessandro; Lambrechts, Michiel; Jacobson, Seth A. (EDP Sciences, 2021)
At least 30% of main sequence stars host planets with sizes of between 1 and 4 Earth radii and orbital periods of less than 100 days.We use N-body simulations including a model for gas-assisted pebble accretion and disk–planet tidal interaction to study the formation of super-Earth systems.We show that the integrated pebble mass reservoir creates a bifurcation between hot super-Earths or hot-Neptunes (.15M) and super-massive planetary cores potentially able to become gas giant planets (&15M). Simulations with moderate pebble fluxes grow multiple super-Earth-mass planets that migrate inwards and pile up at the inner edge of the disk forming long resonant chains. We follow the long-term dynamical evolution of these systems and use the period ratio distribution of observed planet-pairs to constrain our model. Up to 95% of resonant chains become dynamically unstable after the gas disk dispersal, leading to a phase of late collisions that breaks the original resonant configurations. Our simulations naturally match observations when they produce a dominant fraction (&95%) of unstable systems with a sprinkling (.5%) of stable resonant chains (the Trappist-1 system represents one such example). Our results demonstrate that super-Earth systems are inherently multiple (N-2) and that the observed excess of single-planet transits is a consequence of the mutual inclinations excited by the planet–planet instability. In simulations in which planetary seeds are initially distributed in the inner and outer disk, close-in super-Earths are systematically ice rich. This contrasts with the interpretation that most super-Earths are rocky based on bulk-density measurements of super-Earths and photo-evaporation modeling of their bimodal radius distribution.We investigate the conditions needed to form rocky super-Earths. The formation of rocky super-Earths requires special circumstances, such as far more efficient planetesimal formation well inside the snow line, or much faster planetary growth by pebble accretion in the inner disk. Intriguingly, the necessary conditions to match the bulk of hot super-Earths are at odds with the conditions needed to match the Solar System.
Keywords: Methods: numerical; Planet-disk interactions; Planets and satellites: composition; Planets and satellites: detection; Planets and satellites: dynamical evolution and stability; Planets and satellites: formation